How Individual Movement Response to Habitat Edges Affects Population Persistence and Spatial Spread - Maciel, Gabriel Andreguetto; Lutscher, Frithjof (Université d'Ottawa | University of Ottawa, 2013)
How individual-level movement decisions in response to habitat edges influence population-level patterns of persistence and spread of a species is a major challenge in spatial ecology and conservation biology. Here, we integrate novel insights into edge behavior, based on habitat preference and movement rates, into spatially explicit growth-dispersal models. We demonstrate how crucial ecological quantities (e.g., minimal patch size, spread rate) depend critically on these individual-level decisions. In particular, we find that including edge behavior properly in these models gives qualitatively different and intuitively more reasonable results than those of some previous studies that did not consider this level of detail. Our results highlight the importance of new empirical work on individual movement response to habitat edges.
Keywords: edge behavior, spatial heterogeneity, population dynamics, reaction-diffusion equations